The influence of sex offender registration and notification laws on fostering collective identity among offenders - Ten Bensel, Tusty (Journal of crime and justice, 2017)
A collective identity has been ascribed to sex offenders by law, in which everyone on the registry are presumed to be dangerous, at equal risk for reoffending, and deserve extra scrutiny and prohibitions beyond what other types of convicted offenders experience. As a result, sex offenders often experience harassment, social isolation, stigmatization, loss of employment, and homelessness. Such negative experiences may affect their identities or how they come to view themselves. It is then important to determine if sex offenders accept the structurally and culturally collective identity placed upon them and what, if any, methods have been found to mitigate social effects on their identity. This study explored if and how the consequences of registration and notification (RN) laws affected notions of person and perhaps created a collective identity among sex offenders. We conducted interviews with 112 sex offenders and found that they did see themselves part of a collective group, one that was formed over time, exhibited a group level consciousness, and practiced negotiations within the group to change the thoughts and daily lives of members. We believe the results of this study can be used to highlight the need to recognize these identities when planning treatment modalities and determine the future of sex offender laws.